PELATIHAN PENGEMBANGAN PLTMH BERBASIS MASYARAKAT MANDIRI - Djuarensi Patabang; Thomas Pagasis (LPPM Uncen, 2017)
The community service was conducted at the Laboratory of the Faculty of Engineering, Cenderawasih University. The topics is The Development Training of